2014
DOI: 10.1111/cns.12284
|View full text |Cite
|
Sign up to set email alerts
|

N‐(furan‐2‐ylmethyl)‐N‐methylprop‐2‐yn‐1‐amine (F2MPA): A Potential Cognitive Enhancer with MAO Inhibitor Properties

Abstract: Our findings suggest that, the MAO-B inhibitor, F2MPA improves DG synaptic transmission without triggering pathological hyperexcitability. Therefore, F2MPA shows promise as a potential cognition-enhancing therapeutic drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 39 publications
(57 reference statements)
1
19
1
Order By: Relevance
“…Moreover, while 3-MT would generate few off targets on its own 23 Intracerebral microdialysis is a much more sensitive approach for the study of MAO A function compared to tissue measurement as exemplified in this study with clorgyline. The finding that F2MPA altered neither basal nor 3-MT-stimulated extracellular levels of HVA in contrast to clorgyline suggests that the effects reported previously in vivo 12 or in this study ex vivo are unrelated to MAO inhibition. Nonetheless, MAOIs administered acutely have complex and regional effects on monoamine content 13 .…”
Section: Resultscontrasting
confidence: 75%
See 3 more Smart Citations
“…Moreover, while 3-MT would generate few off targets on its own 23 Intracerebral microdialysis is a much more sensitive approach for the study of MAO A function compared to tissue measurement as exemplified in this study with clorgyline. The finding that F2MPA altered neither basal nor 3-MT-stimulated extracellular levels of HVA in contrast to clorgyline suggests that the effects reported previously in vivo 12 or in this study ex vivo are unrelated to MAO inhibition. Nonetheless, MAOIs administered acutely have complex and regional effects on monoamine content 13 .…”
Section: Resultscontrasting
confidence: 75%
“…Based on the previous study reporting a strong effect of F2MPA at 1 mg/kg 12 , we selected the doses of 1 and 4 mg/g for all drugs (Table 1). Although all compounds significantly enhanced 5-HT content in the cortex, the main result is that all compounds exhibited a distinct profile on monoamine tissue content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In detail, scaffolds containing a propargylamine moiety are of particular interest due to their reported beneficial actions 18,19 . In a previous work we have demonstrated that the concurrent inhibition of this enzyme and the binding to the 5-HT3 receptor can lead to interesting compounds 20 .…”
Section: Introductionmentioning
confidence: 99%